2021
DOI: 10.1016/j.heliyon.2021.e08241
|View full text |Cite
|
Sign up to set email alerts
|

Harbor and coastal structures: A review of mechanical fatigue under random wave loading

Abstract: Harbor and coastal structures are essential in maritime connections. Additionally, some offshore structures near the coast are important for supplying energy as a material or transforming the natural resources into energy, as in wind turbines. One of the main issues that needs to be overcome in terms of these structures is mechanical fatigue due to the loads of the structure by its function and waves, wind, the current seawater level, and ice. Structural design has to meet high target loads to ensure that stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 132 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…Ref. [9] employed the ensemble of random Gaussian Laplace eigenfunctions on 3D arithmetic random waves and studied the distribution of their nodal surface area. In their study, they have shown that the nodal area variance follows an asymptotic and thus, the expected area is proportional to the square root of the eigenvalue (energy) of the eigenfunction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [9] employed the ensemble of random Gaussian Laplace eigenfunctions on 3D arithmetic random waves and studied the distribution of their nodal surface area. In their study, they have shown that the nodal area variance follows an asymptotic and thus, the expected area is proportional to the square root of the eigenvalue (energy) of the eigenfunction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wave climate change can greatly affect the life of offshore structures due to its significant alternations during the year, and because it depends on different agents, such as tidal and moon impacts, temperature, typhoons, etc. [60]. Du et al reported that if the simultaneous effects of marine corrosion and wave climate change on fatigue life are overlooked, it is possible that fatigue life evaluation faces up to a 35% error in the long term [61].…”
Section: Reliability and Failure Probabilitymentioning
confidence: 99%
“…In maritime environments, systems are more susceptible to faults than in other environments due to environmental perturbations [ 1 , 2 ], corrosive conditions [ 3 , 4 ], and floating debris [ 5 , 6 , 7 ]. Moreover, recent research on navigational efficiency [ 8 , 9 ], use of renewable energy [ 10 , 11 , 12 , 13 , 14 ], situation awareness [ 11 , 15 ], improved communication methods [ 16 , 17 ], etc., applied to surface platforms is broadening spatial and temporal boundaries for unmanned surface platforms.…”
Section: Introductionmentioning
confidence: 99%